Fragmentation Trade and Vertical Specialisation: How Does South Asia Compare with China. Issue 1 (April 2019) - Veeramani, C.
Abstract: This article analyses the trends and patterns of export and fragmentation trade by South Asian countries—Bangladesh, India, Pakistan and Sri Lanka. To place the discussion in a comparative perspective, the analysis also covers China. Experience of China and other East Asian countries shows that export-led industrialisation and a high degree of participation in global production networks/value chains, based initially on specialisation in labor-intensive activities, are crucial for sustained employment generation and poverty reduction. However, exports have not become a major engine of growth in South Asian countries. An important reason for this is that South Asia has been locked out of the global production networks/value chains in several industries, except Bangladesh and Sri Lanka in readymade garments and India in automobiles. India's export basket is biased towards capital- and skill-intensive products, which is an anomaly as the country's true comparative advantage lies in unskilled labor-intensive activities. We argue that India's labor laws have had the unintended consequence of discouraging specialisation in labor-intensive stages of the production process in manufacturing industries. Greater integration of domestic industries with global production networks/value chains will accelerate the process of shifting the surplus labor from agriculture to manufacturing. JEL Codes: F10, F15, F40